PHENOLIC CONTENT DISTRIBUTION AND ANTIOXIDANT ACTIVITIES OF TERMINALIA SERICEA BURCH - Anokwuru, Chinedu P.; Ramaite, Isaiah D. I.; Bessong, Pascal (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Terminalia sericea has been used traditionally for the treatment of diseases associated with oxidative stress. This study was aimed at determining the distribution of phenols in the leaves, stem bark and root bark of Terminalia sericea and their antioxidant activity. Materials and methods: Hot and cold water, methanol/acetone extracts were evaluated for their total phenolic content (TPC), flavone/flavonol content (FFC), flavonone/dihydroflavone content (FDFC), hydroxycinnamic acid derivative content (HCAC) and tannin content (TC). DPPH (2,2-diphenyl-1-picrylhydrazyl) free radicals and reducing power assays were used to assess the antioxidant activity. Results: The leaves had the highest average TPC (440) expressed in milligram Gallic Acid Equivalent (mgCAE) /gram of the extract. The leaves also had the highest average TC (7.14) expressed in milligram Quercetin Equivalent (mgQE) /gram of the extract. The stem had the highest average FDFC (19.23 mgQE/g) while the root had the highest average FFC (74.76 mgQE/g) and HCAC (214.57) expressed in milligram Caffeic Acid Equivalent mgCAE/ gram of the extract. The stem exhibited the highest average DPPH free radical scavenging (9.85 µg/mL) and reducing power (6.01 µg/mL) activities. Water was a better extracting solvent for TPC and FDFC while methanol/acetone was a better extracting solvent for FFC and HCAC. The correlation between TC and reducing power activity (r=0.668) at P < 0.05 suggests that tannins were responsible for the antioxidant activity. Conclusion: This study has shown that the distribution of phenolics differs in the organs of T. sericea, and could affect the quality of medicinal products sold.